Early Virologic Nonresponse to Tenofovir, Abacavir, and Lamivudine in HIV-Infected Antiretroviral-Naive Subjects - Gallant, Joel E.; Rodriguez, Allan E.; Weinberg, Winkler G.; Young, Benjamin; Berger, Daniel S.; Lim, Michael L.; Liao, Qiming; Ross, Lisa; Johnson, Judy; Shaefer, Mark S. (The Journal of infectious diseases, 2005)
BackgroundAntiretroviral combinations that reduce the number of pills and dosing frequency have the potential to simplify therapy. We compared 2 regimens dosed as 2 pills once daily MethodsThis was a randomized, open-label, multicenter study of tenofovir disoproxil fumarate versus efavirenz, both administered once daily with the abacavir/lamivudine fixed-dose combination in treatment-naive human immunodeficiency virus type 1 (HIV-1)–infected subjects. After reports of early nonresponse, an unplanned interim analysis was performed. Virologic nonresponse was defined as (1) a <2.0-log10 copies/mL decrease in HIV-1 RNA level by week 8, (2) an HIV-1 RNA rebound of ⩾1.0 log10 copies/mL above the nadir, or (3) for subjects with 2 consecutive HIV-1 RNA measurements <50 copies/mL, a subsequent increase to >400 copies/mL on 2 consecutive occasions ResultsWe randomized 340 subjects. Median baseline HIV-1 RNA level and CD4+ cell count were 4.7 log10 copies/mL and 251 cells/mm3, respectively; 194 subjects with HIV-1 RNA data from ⩾8 weeks were included in the interim analysis. Virologic nonresponse occurred in 50 (49%) of 102 subjects in the tenofovir disoproxil fumarate arm, compared with 5 (5%) of 92 of subjects in the efavirenz arm (P<.001). Within 12 weeks, viral genotypes for nonresponders in the tenofovir disoproxil fumarate arm showed M184V or I/M/V mixtures in 40 (98%) of 41 subjects and K65R and M184V or mixtures in 22 (54%) of 41 subjects. The protocol was immediately amended to modify the tenofovir disoproxil fumarate arm. The efavirenz arm continued unchanged; after 48 weeks, 120 (71%) of 169 subjects achieved HIV-1 RNA levels <50 copies/mL ConclusionThe tenofovir disoproxil fumarate/abacavir/lamivudine regimen resulted in an unexpected and unacceptably high rate of nonresponse and incidence of K65R and M184V/I. This 3-drug regimen should not be used